2016
DOI: 10.1037/xge0000223
|View full text |Cite
|
Sign up to set email alerts
|

Impaired generalization of speaker identity in the perception of familiar and unfamiliar voices.

Abstract: In 2 behavioral experiments, we explored how the extraction of identity-related information from familiar and unfamiliar voices is affected by naturally occurring vocal flexibility and variability, introduced by different types of vocalizations and levels of volitional control during production. In a first experiment, participants performed a speaker discrimination task on vowels, volitional (acted) laughter, and spontaneous (authentic) laughter from 5 unfamiliar speakers. We found that performance was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(117 citation statements)
references
References 51 publications
(93 reference statements)
21
96
0
Order By: Relevance
“…These spanned at least one full sentence so that unlike in some previous psychological voice discrimination studies, prosodic information could be used to make a matching decision. As has already been noted, previous studies have tended to use much shorter samples of speech (e.g., Lavan et al, ).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…These spanned at least one full sentence so that unlike in some previous psychological voice discrimination studies, prosodic information could be used to make a matching decision. As has already been noted, previous studies have tended to use much shorter samples of speech (e.g., Lavan et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Task difficulty may increase the likelihood that lay listeners will attribute the variability to the same identity because they lack expert knowledge about how individual voices can vary across instances and are unable to isolate high‐level features of speech that are stable across utterances (Alexander et al, ; Leemann et al, ). From a perceptual point of view, the presence of intraspeaker variability is problematic for lay listeners trying to discriminate between identities (Lavan et al, ; Narayan et al, ; Wester, ). This is supported by the pattern of results observed in these experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that individuals with brain lesions are able to successfully complete speaker discrimination tasks using unfamiliar voices but cannot recognise familiar voices, and vice versa ( Van Lancker & Kreiman, 1987, Van Lancker, Cummings, Kreiman & Dobkin, 1988, Van Lancker, Kreiman, Cummings, 1989; see also Garrido et al, 2009 for a case study of developmental phonagnosia). This evidence is compelling, and conclusively demonstrates that discrimination is not a prerequisite for recognition (Van Lancker & Kreiman, 1987), however manipulations of voice familiarity and task type overlap in these studies (Lavan, Scott & McGettigan, 2016;Maguinness et al, 2017). It is thus unclear whether the findings reflect dissociations in familiar versus unfamiliar voice identity processing per se, differences in task demands, or aspects of both.…”
Section: Combining Hierarchical and Mechanistic Modelsmentioning
confidence: 67%